2013
DOI: 10.1021/ja408587u
|View full text |Cite
|
Sign up to set email alerts
|

Universal Binding Behavior for Ionic Alkyl Surfactants with Oppositely Charged Polyelectrolytes

Abstract: Oppositely charged polyelectrolyte-surfactant mixtures are ubiquitous in biology and the basis of numerous consumer healthcare products. Despite their broad use, however, a rational approach to their formulation remains challenging because of the complicated association mechanisms. Through compilation and analysis of literature reports and our own research, we have developed a semiempirical correlation of the binding strength of surfactants to polyelectrolytes in salt-free mixtures as a function of the polyion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 100 publications
1
70
0
1
Order By: Relevance
“…We previously reported C16-DAPMA as part of a study of ligand effects on polyanion binding. 8d In this new study, we wanted to investigate the impact of hydrophobic chain on self-assembly, heparin binding and nanostructuring it was predicted this should modify polyanion binding, 14 even though the hydrophobic unit is not itself directly involved at the binding interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported C16-DAPMA as part of a study of ligand effects on polyanion binding. 8d In this new study, we wanted to investigate the impact of hydrophobic chain on self-assembly, heparin binding and nanostructuring it was predicted this should modify polyanion binding, 14 even though the hydrophobic unit is not itself directly involved at the binding interface.…”
Section: Resultsmentioning
confidence: 99%
“…13 Li and Wagner tried to consolidate many of these studies and reported universal binding behaviour for ionic alkyl surfactants with polyanions, noting the importance of surfactant hydrophobicity and polymer charge density in controlling cooperative binding strength. 14 It has also been noted that flexibility/rigidity can play important roles in polyelectrolyte binding. 15 With the fundamental interest in this kind of binding process in mind, and also considering the clinical interest in heparin binding for the reversal of anti-coagulation therapy following surgical intervention, we wanted to characterize our SAMul heparin binders in greater structural detail.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Surface tension (ST) analysis is the most popular technique for studying surface activities of surfactants. [4][5][6] While surfactants are generally described as "substances that reduce surface tension", the situation is not so straightforward when other molecules, such as polyelectrolytes, are presented in the solution. [7][8][9] The interaction between the surfactant and the polyelectrolyte produces a complex ST behavior, and a clear interpretation has been difficult.…”
Section: Supporting Information Availablementioning
confidence: 99%
“…In a simplified but still realistic picture, the interactions between surfactant and polymer can be divided into "vertical" and "horizontal" forces: the former between surfactant and polymer, they are mostly of electrostatic nature but also hydrophobic forces and hydrogen bonding play a role; the latter consider the interaction among the surfactant tails, mostly by hydrophobic and dispersion forces. For binding processes following the Satake-Yang isotherm, which is often the case for semi-rigid polysaccharide/surfactant mixtures [38][39][40][41], a detailed calorimetric investigation can highlight the relevance of the different energetic contributions [42]. The outcome of a typical isothermal calorimetric titration for oppositely charged surfactant/ polyelectrolyte mixtures is reported in Fig.…”
Section: Binding Isothermsmentioning
confidence: 99%